Zinc Deficiency and the Recurrence of Clostridium difficile Infection after Fecal Microbiota Transplant: A Retrospective Cohort Study - Blake A. Niccum; Daniel J. Stein; Brian W. Behm; R. Ann Hays (Journal of Nutrition and Metabolism)
Background. Fecal microbiota transplant (FMT) is an effective therapy for recurrent Clostridium difficile infection (CDI). However, in 12% of patients treated with FMT, CDI recurs within one month. Zinc deficiency predicts increased diarrheal frequency in malnourished children, but little is known about its association with FMT outcome. We hypothesized that zinc levels were an independent predictor of CDI recurrence after FMT. Methods. We performed a retrospective cohort study of 80 patients (mean age, 66; 59 women) receiving FMT for CDI from 9/2013–9/2016 at a tertiary care center. Zinc levels were measured within 90 days before FMT. The primary outcome was CDI recurrence within 90 days after FMT. We controlled for risk factors for FMT failure using Cox regression. We also analyzed the effect of zinc supplementation in individuals with deficiency. Results. Forty-nine subjects had a normal zinc level, and 31 had a low level (<0.66 µg/mL). CDI recurred in 3/49 (6%) patients with normal zinc and 5/31 (16%) patients with low zinc (HR = 11.327, 95% CI = 2.162–59.336, p=0.004). Among low zinc subjects, 2 of 25 (8%) that received zinc supplements and 3 of 6 (50%) that did not receive zinc supplements had recurrence of CDI (HR = 0.102, 95% CI = 0.015–0.704, p=0.021). Conclusion. Zinc deficiency was associated with increased CDI recurrence after FMT. Among zinc-deficient patients, supplementation was associated with reduced recurrence. Further study is needed to determine whether zinc deficiency represents a pathophysiologic mechanism and target for therapy.